Polyoxymethylene/thermoplastic polyurethane blends compatibilized with multifunctional chain extender. Issue 4 (19th May 2012) - Tang, Weihua; Wang, Huanhuan; Tang, Jian; Yuan, Huilin
Abstract Novel compatibilized polyoxymethylene/thermoplastic polyurethane (POM/TPU) blends are successfully developed using multifunctional chain extender, Joncryl ADR‐4368, as the compatibilizer. The outstanding compatibilization efficiency of Joncryl on POM/TPU blend was demonstrated by its even higher mechanical properties with only 0.5 wt % of Joncryl than those with 5 wt % of three commonly used compatibilizers. Addition of only 0.5 wt % Joncryl can double the impact strength and significantly improve its tensile strength and flexural strength for POM/TPU (75/25) blend. SEM images show that Joncryl can reduce TPU particle size and enhance the interfacial interactions between POM and TPU. The interparticle distance of TPU in POM/TPU/Joncryl blends was calculated as 0.2 μm, quite close to the critical matrix ligament thickness of POM/TPU blends (0.18 μm). The impact force profile vividly shows that the addition of Joncyl in POM/TPU blends can dramatically increase the total impact energy absorbed by this blend system and enhance the interfacial interactions between POM and TPU. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013